2019
DOI: 10.3390/jcm8111825
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Glucose Metabolism in People with Extremely Elevated High-Density Lipoprotein Cholesterol and Low Alcohol Consumption: Results of the Kanagawa Investigation of Total Checkup Data from the National Database-3 (KITCHEN-3)

Abstract: Background: Recently, we have shown that extremely high high-density lipoprotein cholesterol (HDL-C), which was observed mostly in heavy drinkers, was associated with the incidence of diabetes. However, the observed association was influenced by the consumption of alcohol. Furthermore, it is unknown whether impaired glucose metabolism exists in people with extremely high HDL-C, regardless of their alcohol consumption. Therefore, we addressed this issue in people who did not have a habit of drinking alcohol. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Alternatively, as we previously proposed, 9 another mechanism may exist for the association. Catecholamines, which are over-secreted in pheochromocytoma and paragangliomas, can cause hypertension, diabetes and weight loss.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Alternatively, as we previously proposed, 9 another mechanism may exist for the association. Catecholamines, which are over-secreted in pheochromocytoma and paragangliomas, can cause hypertension, diabetes and weight loss.…”
Section: Discussionmentioning
confidence: 71%
“…[1][2][3] Consistently, cohort studies in recent years have shown that higher mortality rates associated with CVD are observed in individuals with HDL-C levels above 80-100 mg/dL. [4][5][6][7] In addition, we recently demonstrated that people with extremely high HDL-C (EH-HDL; ≥110 mg/dL) have increased risks for diabetes 8 and impaired glucose metabolism equivalent to pre-diabetes, 9 compared with HDL-C 80-89 and 70-79 mg/dL, respectively, which showed a J-shaped or U-shaped association between the levels of HDL-C and impaired glucose metabolism.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…This observation could account for the negative results of trials of entities that enhance HDL-C levels. Further studies of this parabolic relationship have revealed that extremely 3 high HDL-C levels (> 100 mg/dL) are associated with endothelial dysfunction [19,20*], impaired glucose metabolism [21] and an impaired capacity of HDL to acquire free cholesterol from triglyceride-rich lipoprotein lipolysis [22]. Alternatively, extremely high HDL-C levels may be attributed to particular lifestyles such as excessive alcohol consumption, or genomic factors such as loss-of-function mutations in key HDL metabolism-regulating genes [23].…”
mentioning
confidence: 99%